The Internet of Things 20th Tyrrhenian Workshop on Digital Communications - Giusto, Daniel; Iera, Antonio; Morabito, Giacomo; Atzori, Luigi; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This book presents a selection of papers submitted to the 20th Tyrrhenian Workshop, which took place in September 2009 in Sardinia, Italy. The workshop focused on the "Internet of Things." This subject is quickly emerging in the wireless technology arena. It describes the pervasive presence of a variety of devices$1 (Bsuch as sensors, actuators, and mobile phones$1 (Bwhich, through unique addressing schemes, are able to interact and cooperate with each other to reach common goals. This novel paradigm, which originated from the idea of "smart" environments, will be sure to impact the future of logistics, Intelligent Transportation Systems, business and process management, assisted living, E-health, and other applications. The Internet of Things covers a wide array of essential topics related to this emerging paradigm, including infrastructures and applications, communication systems and network architectures, embedded systems, and location and tracking through navigation sensors. It also addresses the technological and social implications of this technology, as well as challenges that may arise.s
Networking Issues -- Objects Communication Behavior on Multihomed Hybrid Ad Hoc Networks -- Classification of Emerging Protocols in the Presence of Asymmetric Routing -- Performance Evaluation of Routing Protocols in WSNs Arranged in Linear Topologies -- A Distributed Procedure for IEEE 802.15.4 PAN Coordinator Election in Emergency Scenarios -- A Mobile Platform for Measurements in Dynamic Topology Wireless Networks -- Cluster-Based Irresponsible Forwarding -- Dynamic Spectrum Access Communications: Wavelet Modulation with Unequal Power Allocation -- Optimal Cross-Layer Flow-Control for Wireless Maximum-Throughput Delivery of VBR Media Contents -- A Secure MPLS VPN Infrastructure for Complex Geodata Sensor Network -- The Role of the Middleware -- Making the Internet of Things a Reality: The WhereX Solution -- A Scalable Grid and Service-Oriented Middleware for Distributed Heterogeneous Data and System Integration in Context-Awareness-Oriented Domains -- InterDataNet: A Scalable Middleware Infrastructure for Smart Data Integration -- CONVERGENCE: Extending the Media Concept to Include Representations of Real World Objects -- Service Oriented Middleware Solutions for Emergency Communication Networks -- Localization and Applications -- Localization Issues in a ZigBee Based Internet of Things Scenario -- Low-Complexity Audio Signal Processing for Localization in Indoor Scenarios -- Integrated GPS-Denied Localization, Tracking, and Personal Identification -- Design and Implementation of Smartphone Applications for Speaker Count and Gender Recognition -- Video Coding with Motion Estimation at the Decoder -- Inter-Vehicle Communication QoS Management for Disaster Recovery -- RFID and Sensor Networks Technologies -- Beyond the ID in RFID -- Performance Characterization of Passive UHF RFID Tags -- Chipless Tags, the Next RFID Frontier -- Backscatter Communication Using Ultrawide Bandwidth Signals for RFID Applications -- Passive RFID Integrated Transponders for Automotive Applications -- Sensor-Oriented Passive RFID -- Performance Evaluation of UHF RFID Tags in the Pharmaceutical Supply Chain -- The Benefits of RFID and EPC in the Supply Chain: Lessons from an Italian Pilot Study -- RFID Data Analytics in Apparel Retail -- Towards the Future Internet of Sensors -- Energy and Distortion Minimization in (3z(BRefining(3y (Band (3z(BExpanding(3y (BSensor Networks -- An IEEE 802.15.4 Wireless Sensor Network for Energy Efficient Buildings -- A Real Implementation and Deployment for Wine Production Management Based on Wireless Sensor Network Technology -- Performance Evaluation of an IEEE802.15.4 Standard Based Wireless Sensor Network in Mars Exploration Scenario -- The PECES Project: Ubiquous Transport Information Systems -- HYDRA: A Development Platform for Integrating Wireless Devices and Sensors into Ambient Intelligence Systems -- Probabilistic Information Dissemination for MANETs: The IPAC Approach -- Security and Privacy Issues -- An Overview of Privacy and Security Issues in the Internet of Things -- Privacy Challenges in RFID Systems -- Security and Privacy Protection of Contactless Devices -- Private Location-Based Information Retrieval via k-Anonymous Clustering.s
Keywords: Engineering; Computer network architectures; Telecommunication; Engineering; Communications Engineering, Networks; Computer Systems Organization and Communication Networks